Dietary intake mediates the relationship of body fat to pain. Issue 2 (February 2017) - Emery, Charles F.; Olson, KayLoni L.; Bodine, Andrew; Lee, Victoria; Habash, Diane L.
Abstract : Abstract: Prior studies have documented an association of obesity with chronic pain, but the mechanism explaining the association remains unknown. This study evaluated the degree to which dietary intake of foods with anti-inflammatory effects mediates the relationship of body fat to body pain. Ninety-eight community-residing healthy adults (60% women; mean age = 43.2 ± 15.3 years; range: 20-78 years) participated in a home-based study of home environment, food-related behaviors, health, and adiposity. During a 3-hour home visit evaluation, 3 measures of body fat were collected, including height and weight for calculation of body mass index (BMI). Participants also completed a 24-hour food recall interview and self-report measures of bodily pain (BP; BP subscale from the Medical Outcomes Study Short Form-36) and psychological distress (Hospital Anxiety and Depression Scale). Quality of dietary intake was rated using the Healthy Eating Index-2010. Mediation models were conducted with the PROCESS macro in SAS 9.3. Mean BMI was consistent with obesity (30.4 ± 7.8; range: 18.2-53.3), and BP values (73.2 ± 22.1; range: 0-100) and dietary intake quality (59.4 ± 15.5; range: 26.8-88.1) were consistent with population norms. Modeling in PROCESS revealed that Healthy Eating Index-2010 scores mediated the relationship between BMI and BP ( b indirect = −0.34, 95% confidence interval = −0.68 to −0.13). The mediation model remained significant when controlling for biomechanical factors (arthritis/joint pain), medication use, psychological distress, age, and education, and models remained significant using the other 2 body fat measures. Thus, the data indicate that dietary intake of foods with anti-inflammatory effects mediates the relationship of body fat to body pain in healthy men and women. Abstract : Dietary intake of foods with anti-inflammatory effects mediated the relationship between body fat and generic bodily pain in healthy, community-residing adults.